Development and application of bio-economic modelling to compare silvoarable, arable and forestry systems in three European countries - Palma, J.H.N. (2010)
Silvoarable agroforestry could promote use of trees on farms in Europe, but its likely effect on production, farm profitability, and environmental services is poorly understood. Hence, from 2001 to 2005, the Silvoarable Agroforestry for Europe project developed a systematic process to evaluate the biophysical and economic performance of arable, forestry, and silvoarable systems in Spain, France, and The Netherlands. A biophysical model called “Yield-SAFE” was developed to predict long-term yields for the different systems and local statistics and expert opinion were used to derive their revenue, costs, and pre- and post-2005 grant regimes. These data were then used in an economic model called “Farm-SAFE” to predict plot- and farm-scale profitability. Land equivalent ratios were greater than one, showing Yield-SAFE predicted that growing trees and crops in silvoarable systems was more productive than growing them separately. Pre-2005 grants in Spain and The Netherlands penalised silvoarable systems, but post-2005 grantswere more equitable. In France,walnut and poplar silvoarable systems were consistently the most profitable system under both grant regimes. In Spain, holm oak and stone pine silvoarable systemswere the least profitable system under pre-2005 grants, but only marginally less profitable than arable systems under post-2005 grants. In The Netherlands, low timber values and the opportunity cost of losing arable land for slurry manure application made silvoarable and forestry systems uncompetitive with arable systems under both grant regimes.